The Ritual of “Encircling the Tomb” in the Funerary Monument of Djehuty (TT 11) - Serrano, José M. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
In the Theban tomb of Djehuty (TT 11) we have the representation of a ritual apparently focused on surrounding the funerary monument. The objective of this paper is the reconstruction of the scene, and the text that accompanies it, thanks to the parallel of TT 20 (Montuherkhepeshef). This allows us to link this ritual to the Pap. Ramesseum E and other antecedents of the Old and Middle Kingdom. An interpretation within the historical, religious and cultural context of the age of Hatshepsut-Thutmose III, and a possible relationship with the Middle Egypt background of the owners of TT 11 and TT 20 is also proposed.